2003
DOI: 10.1159/000071868
|View full text |Cite
|
Sign up to set email alerts
|

The Calpain-Calpastatin System and the Calcium Paradox in the Isolated Perfused Pigeon Heart

Abstract: To examine whether the calpain-calpastatin system is activated during the calcium paradox in the isolated perfused pigeon heart, we separated the protease from its inhibitor calpastatin and studied its kinetic properties. The protease exhibits kinetic properties similar to those of mammalian m-calpains. Ca2+ requirements for half and maximum activities are 220 µM and 2 mM, respectively. In the absence of Ca2+ the protease is strongly activated by Mn2+ or Sr2+. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…In the present study, we found increased calpain‐mediated degradation of α‐fodrin during Ca 2+ repletion, which was attenuated by the selective calpain inhibitor MDL 28170. These findings are indicative of calpain activation during the Ca 2+ paradox and are consistent with those of a previous study that reported increased in vitro cleavage products of denatured casein by extracts from Ca 2+ ‐paradoxic hearts . Moreover, confocal image analysis showed the translocation of both μ‐ and m‐calpain to the sarcolemmal membrane during Ca 2+ repletion, suggesting that both isoforms contribute to Ca 2+ paradox‐induced heart injury.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In the present study, we found increased calpain‐mediated degradation of α‐fodrin during Ca 2+ repletion, which was attenuated by the selective calpain inhibitor MDL 28170. These findings are indicative of calpain activation during the Ca 2+ paradox and are consistent with those of a previous study that reported increased in vitro cleavage products of denatured casein by extracts from Ca 2+ ‐paradoxic hearts . Moreover, confocal image analysis showed the translocation of both μ‐ and m‐calpain to the sarcolemmal membrane during Ca 2+ repletion, suggesting that both isoforms contribute to Ca 2+ paradox‐induced heart injury.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, other proteins, including Na + /K + ‐ATPase and nitric oxide synthase, have been shown to be targets of calpain activation in the heart . A previous study in pigeon hearts demonstrated that the Ca 2+ paradox may trigger a transient increase in calpain activity . However, it has not been determined whether calpain mediates Ca 2+ paradox‐induced heart injury and, if so, which isoform of calpain is involved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calcium overload associated with ischemia and reperfusion activates calpains and reduces calpastatin levels (17, 18). Until recently, no in vivo studies have examined calpain regulation of the NF-κB pathway during reperfusion of immature myocardium.…”
Section: Discussionmentioning
confidence: 99%
“…Although the amount of Ca 2+ required for the in vitro activation of μ-calpain and m-calpain was different and m-calpain was regulated by binding to phosphatidylinositol 4,5-bisphosphate [12], [13], ample studies have shown that calpains are activated during ischemia/reperfusion, resulting in the cleavage of its substrates, such as Na + /K + -ATPase, α-fodrin, a prominent component of the membrane skeleton, and consequently heart injury [16], [17], [18], [19]. We and others have previously found that after Ca 2+ repletion, calpains are activated and both μ- and m-calpain are anchored to the sarcolemmal membrane [20], [21]; moreover, the addition of MDL28170, an inhibitor of calpain, reduced the cleavage of α-fodrin and rescued myocardial dysfunction and cell death [20]. However, MDL28170 did not substantially reduce the level of LVEDP and the degradation of troponin I [20], a regulatory protein involved in maintaining the diastolic state.…”
Section: Introductionmentioning
confidence: 99%